Development Of A Catalytic Membrane Reactor For The Production Of Ethylene Using Oxidative Coupling Of Methane (Oem) - Chua, Yen Thien (2006)
A catalytic membrane reactor resembles shell and tube heat exchanger integrated with a tubular ceramic membrane was developed for the application in oxidative coupling of methane (OCM) reaction. A 3-components catalyst system (Na-W-Mn/Si02) was used to study the OCM reaction in a packed bed catalytic reactor. The effects of various operating parameters were studied using design of experiments method. The interaction effects of each parameter were obtained and response surface methodology coupled with central composite design was applied in determining the optimum condition. The predicted optimum condition of temperature 850oe, gas hourly space velocity at 23,947cm3/g.hr, catalyst pretreatment period of 2 hrs, CH" to O2 ratio 7 and dilution ratio 0.2 gave 40.55% methane conversion, 79.51 % C2+ selectivity and 32.24% C2+ yield. The experimental value of with 43.05% methane conversion, 70.62% C2+ selectivity and 30.40% C2+ yield was obtained at an optimum condition.